Crystal structure and luminescence properties of a novel red Ca3GdNa(PO4)3F:Eu3+ phosphor for white LEDs. (November 2018) - Wu, Xiulan; Bai, Wenni; Hai, Ou; Ren, Qiang; Lin, Fei; Jiao, Yehui
Highlights: A new host-sensitized Eu 3+ -doped Ca3 GdNa(PO4 )3 F phosphor was firstly synthesized. Ca3 GdNa(PO4 )3 F:xEu 3+ phosphors exhibit strong red emission under 395 nm. The phosphor shows high color purity and good color stability. Abstract: A series of Eu 3+ doped novel Ca3 GdNa(PO4 )3 F phosphors have been prepared via a high temperature solid state reaction. The crystal structure, morphology and luminescence properties were studied. The excitation spectra showed that samples can be efficiently excited by 395 nm, which indicated that it can be used for NUV LEDs. The PL spectra showed that the optimal doping concentration of Eu 3+ was 0.6. The quenching mechanism was determined to be the dipole–dipole interaction between Eu 3+ ions. The CIE value of Ca3 GdNa(PO4 )3 F:0.6Eu 3+ sample reaches (0.654, 0.346), which is close to the NTSC standard (0.67, 0.33). In addition, the phosphor has a relatively high quantum efficiency of 40%. The results suggest that the prepared phosphors combined other phosphor or chips will have a potential application in w-LEDs.